2021
DOI: 10.1016/j.isci.2021.103221
|View full text |Cite
|
Sign up to set email alerts
|

An integrated multi-omic analysis of iPSC-derived motor neurons from C9ORF72 ALS patients

Abstract: HighlightsMulti-omic analysis of differentiated C9ORF72 iPSC-derived motor neurons Network-based integrative computational analysis Pathogenic versus compensatory pathways elucidated using C9ORF72 Drosophila model Pathways confirmed with alternative differentiation protocol and postmortem data

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 126 publications
0
13
0
Order By: Relevance
“…In recent years, omics technologies have significantly contributed to uncover the biological heterogeneity of Amyotrophic lateral sclerosis (ALS) [ 114 ]. Recent work has combined iPSCs-derived motor neurons generated from different patients with a common ALS mutation with omics datasets to identify known and novel pathways, which were consistently dysregulated across all lines with the aim to include an additional 1,000 ALS-derived iPSC lines to define the molecular pathogenic signature for ALS [ 93 ]. Similar approach could be applied to characterise iPSCs-based models derived from patients with different stroke types to learn about early pathogenic events and develop new personalised treatments.…”
Section: Current and Potential Applications Of Human Ipscs In Functio...mentioning
confidence: 99%
“…In recent years, omics technologies have significantly contributed to uncover the biological heterogeneity of Amyotrophic lateral sclerosis (ALS) [ 114 ]. Recent work has combined iPSCs-derived motor neurons generated from different patients with a common ALS mutation with omics datasets to identify known and novel pathways, which were consistently dysregulated across all lines with the aim to include an additional 1,000 ALS-derived iPSC lines to define the molecular pathogenic signature for ALS [ 93 ]. Similar approach could be applied to characterise iPSCs-based models derived from patients with different stroke types to learn about early pathogenic events and develop new personalised treatments.…”
Section: Current and Potential Applications Of Human Ipscs In Functio...mentioning
confidence: 99%
“…In particular, cells from the central nervous system are difficult to obtain by biopsy; therefore, iPSCs can be useful for disease modeling. Many reports have shown that disease modeling is successful when using iPSCs, including Alzheimer’s disease (AD) [ 23 , 24 ], Parkinson’s disease [ 25 , 26 ], amyotrophic lateral sclerosis (ALS) [ 27 , 28 ], and schizophrenia [ 29 , 30 ]. In addition to diseases involving heart and nerve cells, diseases in most organs can be modeled using disease-specific iPSC technology.…”
Section: Patient-specific Ipscsmentioning
confidence: 99%
“…For iPSCs-ALS-MNs, the application of computational techniques such as integrated multi-omic analysis resulted in the identification of novel and known aberrant cellular pathways (Li et al, 2021). Integrated multi-omic analysis distinguished pathogenic versus compensatory disease phenotype pathways, which allows for clearer understanding of disease mechanisms.…”
Section: The Role Of Bioinformatics Perspectives and Futurementioning
confidence: 99%